Cyanosis as Mortality Risk among Children with Severe Pneumonia - Herza Fadlinda; Adi Utomo; Henni Djuhaeni (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Pneumonia is the second leading cause of infant death in Indonesia. The mortality of pneumonia in children is associated with cyanosis, malnutrition, and age less than 4 months. The aim of this study was to determine the relationship between cyanosis, malnutrition, and age less than 4 months with the mortality of infant patients with severe pneumonia at Dr Hasan Sadikin General hospital.Methods: A case-control study has been conducted using medical records of 80 patients with pneumonia at Dr. Hasan Sadikin General Hospital, period January 2007 to December 2013. The inclusion criteria were medical records consisting of information about infants with severe pneumonia, without comorbid diagnoses, who died during hospitalization. While controls were infants who have been discharged from hospital. The independent variables of this study were cyanosis, malnutrition, and age less than 4 months, while the dependent variable was the mortality. Data were analyzed by using univariate and bivariate analysis.Results: The study reported that only cyanosis was associated with mortality. Malnutrition and age less than 4 months were not associated with mortality.Conclusions: Cyanosis is known to be the only factor that has affected the mortality of infants with pneumonia who are hospitalized at Dr. Hasan Sadikin General Hospital. [AMJ.2016;3(2):186–9]DOI: 10.15850/amj.v3n2.799